2015
DOI: 10.1016/j.jaci.2015.03.009
|View full text |Cite
|
Sign up to set email alerts
|

A novel hypomorphic mutation in STIM1 results in a late-onset immunodeficiency

Abstract: tours.fr. This work has been funded with support from the French Higher Education and Research Ministry under the program ''Investissements d'avenir'' (grant agreement no. LabEx MAbImprove ANR-10-LABX-53-01). Disclosure of potential conflict of interest: H. Watier has received research support from the French Higher Education and Research Ministry under the program ''Investissements d'avenir'' (grant agreement no. LabEx MAbImprove ANR-10-LABX-53-01). B. Chaigne declares that he has no relevant conflicts of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 8 publications
6
51
0
Order By: Relevance
“…T cells of patients with null muations in ORAI1 or STIM1 lack SOCE and IL-2 production upon TCR stimulation. However, addition of exogenous IL-2 has had variable effects on their ability to proliferate in vitro (Feske et al, 1996; Fuchs et al, 2012; Picard et al, 2009; Schaballie et al, 2015). Similarly, the proliferation of murine T cells lacking STIM1 and STIM2 could not be restored by exogenous IL-2 in vitro and they failed to proliferate in response to LCMV infection in vivo even when transferred to immunocompetent (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…T cells of patients with null muations in ORAI1 or STIM1 lack SOCE and IL-2 production upon TCR stimulation. However, addition of exogenous IL-2 has had variable effects on their ability to proliferate in vitro (Feske et al, 1996; Fuchs et al, 2012; Picard et al, 2009; Schaballie et al, 2015). Similarly, the proliferation of murine T cells lacking STIM1 and STIM2 could not be restored by exogenous IL-2 in vitro and they failed to proliferate in response to LCMV infection in vivo even when transferred to immunocompetent (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the proposed mechanisms involve regulation of the ‘growth factor’ interleukin-2 (IL-2) and cyclins or cyclin-dependent kinases, which in some cell types depend on calcineurin and NFAT signaling (Mognol et al, 2016). Although IL-2 promotes T cell proliferation in vitro in an auto- or paracrine fashion, addition of exogenous IL-2 to T cells from patients with null mutations in ORAI1 or STIM1 or T cells from Orai1 fl/fl Cd4Cre Orai2 −/− mice only weakly rescues TCR-induced proliferation in vitro (Feske et al, 1996; Fuchs et al, 2012; Le Deist et al, 1995; Picard et al, 2009; Schaballie et al, 2015; Vaeth et al, 2017). Another possible mechanism by which SOCE may control T cell proliferation is through the regulation of metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Upon Ca 2+ depletion in the SR, the SOCE pathway is activated to replenish the cytosolic Ca 2+ stores, which is important during prolonged tetanic stimulation and fatigue [43,52,53,54,55,56,57]. The luminal cEFh domain of STIM1 loses the Ca 2+ binding and undergoes conformational changes to the unfolded form, exposing hydrophobic residues [58,59].…”
Section: Store-operated Calcium Entrymentioning
confidence: 99%
“…Affected individuals with loss-of-function mutations in these genes are known to have severe combined immunodeficiency (SCID), characterized by a defect in T-cell activation, recurrent infections [43,45,46], ectodermal dysplasia [47,48], abnormal enamel [43,45,47,52], and muscle hypotonia [43,52,54,56,57]. Transgenic mice with muscle-specific expression of dominant negative ORAI1 have been reported to exhibit reduced body weight, muscle mass, and fiber cross-sectional area [58].…”
Section: Store-operated Calcium Entrymentioning
confidence: 99%
“…Chou and coauthors 41 presented a patient with refractory cytomegalovirus infection and hypotonia, with normal T cell number and mitogen-stimulated proliferation, in whom a frameshift mutation in calcium release-activated calcium modulator 1 (ORAI) was found. Schaballie et al 42 reported two siblings with recurrent infections, refractory inflammatory colitis, psoriasis and myopathy. They identified a homozygous missense mutations in stromal interaction molecule 1 (STIM1) resulting in residual expression and function.…”
Section: Clinical Immunological Phenotypes Associated With Gene Mutatmentioning
confidence: 99%